Experimental study of energy absorption capability of metallic-palm fiber-metallic hybrid composite plate - Aminanda, Yulfian; Hamid, Wan Luqman Hakim (Trans Tech publication, 2011)
An experimental campaign on metallic-palm fiber-metallic hybrid subjected to impact loading using spherical projectile has been carried out. High initial energy impact with projectile mass of 24 kg and speed of 1, 3 and 5 mm/s, has been set enabling to determine the energy absorption capability of hybrid composite panel. The influence of stacking sequences metallic-palm-fiber-metallic and metallic-palm fiber-metallic-palm fiber-metallic with different thickness of metallic and palm fiber, to the energy absorption were investigated. The effect of different striker radius; 10, 13 and 20 mm were carried out as well. The mechanism of failure and energy absorbed by the hybrid composite panel and its components; metallic alone and palm fiber alone, were carried out to understand the advantage of having hybrid structure. The optimum configuration of hybrid panel in term of stacking sequence to absorb the energy of impact is proposed. The methodology of this study can be used for designing the armor to absorb the energy of projectile using palm fiber composite panel.